The contribution of emotion and cognition to moral sensitivity: a neurodevelopmental study - Decety, Jean; Michalska, Kalina J; Kinzler, Katherine D (Cerebral cortex (New York, N.Y. 1991), 2012)
Whether emotion is a source of moral judgments remains controversial. This study combined neurophysiological measures, including functional magnetic resonance imaging, eye-tracking, and pupillary response with behavioral measures assessing affective and moral judgments across age. One hundred and twenty-six participants aged between 4 and 37 years viewed scenarios depicting intentional versus accidental actions that caused harm/damage to people and objects. Morally, salient scenarios evoked stronger empathic sadness in young participants and were associated with enhanced activity in the amygdala, insula, and temporal poles. While intentional harm was evaluated as equally wrong across all participants, ratings of deserved punishments and malevolent intent gradually became more differentiated with age. Furthermore, age-related increase in activity was detected in the ventromedial prefrontal cortex in response to intentional harm to people, as well as increased functional connectivity between this region and the amygdala. Our study provides evidence that moral reasoning involves a complex integration between affective and cognitive processes that gradually changes with age and can be viewed in dynamic transaction across the course of ontogenesis. The findings support the view that negative emotion alerts the individual to the moral salience of a situation by bringing discomfort and thus can serve as an antecedent to moral judgment.